The Semantics Analysis of the Selected Billboards - Ullah, Shakir (University of Chitral Journal of Linguistics and Literature, 2023)
The aim of this study is to delves into a comprehensive analysis of diverse billboard advertisements, uncovering intricate linguistic, cultural, and societal nuances embedded within their messaging strategies. To obtained the objectives of the research, the researchers collected the data in the form of photographing in Sawari bazar, District Buner. The framework used in this study was the proposed concept of Saussure (1956) which contains sign: signifier and signified. The study revealed that these billboards were used to grab readers’ mind attentively and involved them in the displayed items. The research unraveled billboards representing a narrative of modernity, international appeal, and brand association with renowned personalities, transcending national boundaries. Additionally, the healthcare sector, revealing a complex interplay between medical claims, societal beliefs, and cultural notions. It also illuminates the multidimensional nature of billboard advertising, underscoring how these visual and linguistic mediums not only sell products but also serve as reflections of societal aspirations and cultural norms.